Renin-angiotensin-aldosterone system peptide profiles in patients with COVID-19. Issue 4 (April 2021) - Kutz, Alexander; Conen, Anna; Gregoriano, Claudia; Haubitz, Sebastian; Koch, Daniel; Domenig, Oliver; Bernasconi, Luca; Mueller, Beat; Schuetz, Philipp
Abstract : Objective: While evidence on the interface between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the renin-angiotensin-aldosterone-system (RAAS) is accumulating, clinical data on RAAS peptide alteration among coronavirus disease-19 (COVID-19) patients is missing. Design and methods: In this exploratory study, we prospectively included adult patients (aged ≥ 18 years) admitted between February 26 and April 30, 2020 to a tertiary care hospital in Switzerland. We assessed the association of an underlying SARS-CoV-2 infection and equilibrium serum levels of RAAS peptides in hospitalized COVID-19 patients 1:1 propensity-score matched with patients suffering from SARS-CoV-2-negative respiratory infections. Subgroup analyses involved stratification for taking RAAS inhibitors. Results: COVID-19 patients had about 50% lower equilibrium serum RAAS peptide levels as compared with matched controls (angiotensin I: 31.6 vs 66.8 pmol/L, −52.7% (95%CI: −68.5% to −36.9%); angiotensin II: 37.7 vs 92.5 pmol/L, −59.2% (95%CI: −72.1% to −46.3%); angiotensin (1–5): 3.3 vs 6.6 pmol/L, −49.7% (95%CI: −59.2% to −40.2%); angiotensin (1–7): 4.8 vs 7.6 pmol/L, −64.9% (95%CI: −84.5% to −45.3%)). While the plasma renin activity was lower in COVID-19 patients (88.6 vs 207.9 pmol/L, −58.5% (95%CI: −71.4% to −45.6%)), there was no difference of angiotensin-converting enzyme (ACE) and ACE2 plasma activity between the groups. Subgroup analyses revealed a pronounced RAAS peptide profile depression in COVID-19 patients among those not on RAAS inhibitors. Conclusions: As compared with SARS-CoV-2-negative patients, we found a downregulated RAAS in presence of a SARS-CoV-2 infection. Whether the lower levels of the protective angiotensin (1–5) and (1–7) are linked to adverse outcomes in COVID-19 warrants further investigation.